2010
DOI: 10.1021/la903927w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Stabilizer Concentration on the Internal Liquid Crystalline Order and the Size of Oil-Loaded Monolinolein-Based Dispersions

Abstract: The internal phase of monolinolein-based dispersions loaded with tetradecane or (R)-(+)-limonene was investigated as a function of the stabilizer content by small-angle X-ray scattering. Phase transitions at the colloidal scale were found in some of nanostructured aqueous dispersions by increasing the stabilizer content. For particles containing a bicontinuous cubic phase, a large increase of the stabilizer concentration promoted a liquid crystalline phase transition from the Pn3m to the Im3m cubic symmetry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 46 publications
6
37
0
Order By: Relevance
“…For instance, the internal self-assembly of nanostructured emulsions can be altered from cubic Pn3m to cubic Im3m by adding diglycerol monooleate or pluronic F127 to a DU lipid system [111,112]. The size of lipid nanoparticles can be modulated by changing the concentration of the dispersed phase and/or the shear rate of the shearing device [94].…”
Section: Modulating Structure and Properties Of Lipid Systemsmentioning
confidence: 99%
“…For instance, the internal self-assembly of nanostructured emulsions can be altered from cubic Pn3m to cubic Im3m by adding diglycerol monooleate or pluronic F127 to a DU lipid system [111,112]. The size of lipid nanoparticles can be modulated by changing the concentration of the dispersed phase and/or the shear rate of the shearing device [94].…”
Section: Modulating Structure and Properties Of Lipid Systemsmentioning
confidence: 99%
“…In fact, the amphiphilic triblock copolymer, Pluronic F -127 (PEO 99 -PPO 67 -PEO 99 ), hereafter simply F -127, has been most widely used for structured emulsions such as ISAsomes (Guillot et al, 2010 ;Gustafsson et al, 1996Gustafsson et al, , 1997; nevertheless, polysaccharide -and polyethyleneglycol -based stabilizers (Huynh et al, 2009 ) are also used with varying levels of success. In fact, the amphiphilic triblock copolymer, Pluronic F -127 (PEO 99 -PPO 67 -PEO 99 ), hereafter simply F -127, has been most widely used for structured emulsions such as ISAsomes (Guillot et al, 2010 ;Gustafsson et al, 1996Gustafsson et al, , 1997; nevertheless, polysaccharide -and polyethyleneglycol -based stabilizers (Huynh et al, 2009 ) are also used with varying levels of success.…”
Section: Isasomes: Formation and Characterizationmentioning
confidence: 99%
“…It is known that the addition of diglycerol monooleate, or F -127, converts Pn3m into Im3m (Guillot et al, 2010 ;Yaghmur et al, 2006a ), the latter also controls the size of the ISAsomes. It is known that the addition of diglycerol monooleate, or F -127, converts Pn3m into Im3m (Guillot et al, 2010 ;Yaghmur et al, 2006a ), the latter also controls the size of the ISAsomes.…”
Section: Isasomes: Formation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of water five additional phases are formed, fluid lamellar phase, three bicontinous cubic phases, Ia3d, Pn3 m and Im3 m and hexagonal phase (H 2 ) [14]. However, the phase diagrams of monoglyceride mixtures in the presence of different oil have been studied [15][16][17][18][19][20]. Otto Glatter's group found that the bulk phases of oil -loaded monoglyceride-basesd particles depend strongly on the amount of oil [21,22], and the size of the reverse micelles increases with alkyl chain length of oils [23].…”
Section: Introductionmentioning
confidence: 99%